Practical control of underactuated ships - Do, Khac Duc (Elsevier, 2010)
This paper presents a design of global smooth controllers that achieve the practical stabilization of arbitrary reference trajectories, including fixed points and nonadmissible trajectories for underactuated ships. These ships do not have an independent actuator in the sway axis. The control design is based on several nonlinear coordinate changes, the transverse function approach, the back-stepping technique, the Lyapunov direct method, and utilization of the ship dynamics. Simulation results illustrate the effectiveness of the proposed control design. © 2010 Elsevier Ltd.